Incidence of Down Syndrome by maternal age in Chinese population - Song, Yi; Jieping, Song; Tianshu, Zhou; Zhijun, Zhang; Jingxuan, Zhang; Bo, Wang (Frontiers in Genetics, 2022)
Abstract: Objective: This study aims to estimate the maternal age-related risk of Down syndrome in an Asian population. Methods: We performed a retrospective data analysis including a total of 206295 pregnant women who presented for second-trimester maternal serum screening for Down syndrome at Hubei Maternal and Child Health Hospital for the years 2008 to 2017. Cases were assigned to three groups: ≤26 years of age, 27-33 years of age, and ≥34 years of age. The incidence of Down Syndrome was calculated for each age group. The differences between groups were tested using the chi-square (χ2) test. Results: The incidence of Down syndrome in women ≤26 years of age, 27-33 years of age, and ≥34 years of age was 0.67 ‰, 0.29 ‰, and 2.07 ‰ respectively. Statistically significant difference was found between the three age groups (χ2 = 79.748, P < 0.05). Conclusion: Down syndrome rate was significantly higher in women ≥34 years of age. Younger women (≤26 years of age) had a significantly higher risk for Down's syndrome, compared to women aged 27-33.